ISOLASI DAN UJI AKTIVITAS DAYA HAMBAT EKSTRAK ETANOL BIJI PINANG (Areca catechu L.) TERHADAP BAKTERI PADA LIDAH - Djohari, Meiriza; Putri, Wulandari Yulia; Pratiwi, Erniza (Jurnal Riset Kefarmasian Indonesia, 2019)
Betel nut (Areca catechu L.) is a natural material that has antibacterial activity in treating diseased on teeth, halitosis and can inhibit of dental caries. The objective of this research is type of bacteria based on morphology, the results of bacterial identification tests on the tongue and to determine the effect of the inhibitory power of betel nut ethanol extract (Areca catechu L.) to bacteria of the tongue. Antibacterial activity testing using disc diffusion method with various concentrations of 10%, 20% and 30%. Secondary metabolite contents are alkaloid, terpenoid and flavonoid.The results obtained from the identification test based on the color of bacteria Branhamella catarrhalis, Staphylococcus epidermidis and Straphylococcus aureus. Ethanol extract of areca nut (Areca catechu L.) is better to inhibiting the growth of Staphylococcus epidermidis and Staphylococcus aureus compared to Branhamella catarrhalis. Based on Two Way Anova statistical data on inhibitory zone diameters, there were differences between the concentration groups of 10%, 20% and 30% and there were significant differences in the inhibitory activity of Branhamella catarrhalis bacteria compared to Staphylococcus epidermidis and Straphylococcus aureus bacteria but not significantly different between Staphylococcus epidermidis and Straphylococcus aureus bacteria